2015
DOI: 10.1037/pha0000028
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative stimulus effects of morphine and oxycodone in the absence and presence of acetic acid in male and female C57Bl/6 mice.

Abstract: The use of prescription opioids for clinical management of pain remains problematic because of concerns about addiction associated with opioid use. Another difficulty in pain management is the increasing evidence for sex differences in pain behavior and opioid-induced behavioral effects. However, few studies have documented the abuse potential of prescription opioids as a function of pain in rodents, with significant gaps in the literature pertaining to sex differences in the interaction between pain and opioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Morphine and oxycodone were also studied in C57/Bl/6 male and female mice trained to discriminate morphine from saline (Neelakantan et al, 2015) completely for morphine at equipotent doses in both sexes. Walentiny et al (2019) also trained C57Bl/6 mice to discriminate 1.3 mg/kg, s.c. oxycodone from vehicle using a fixed-ratio 10 schedule of food presentation.…”
Section: E Drug Discriminationmentioning
confidence: 99%
“…Morphine and oxycodone were also studied in C57/Bl/6 male and female mice trained to discriminate morphine from saline (Neelakantan et al, 2015) completely for morphine at equipotent doses in both sexes. Walentiny et al (2019) also trained C57Bl/6 mice to discriminate 1.3 mg/kg, s.c. oxycodone from vehicle using a fixed-ratio 10 schedule of food presentation.…”
Section: E Drug Discriminationmentioning
confidence: 99%
“…Multiple studies show that morphine is more efficacious in males in a variety of pre-clinical anti-nociception models. These include; inflammatory models (Loyd et al, 2008, visceral models (Ji et al, 2006, Neelakantan et al, 2015, tail-flick (Kepler et al, 1989, Kest et al, 1999, and hotplate assays (Cicero et al, 1997, Posillico et al, 2015. In humans, the existence of sex differences in μ receptor analgesia is controversial, with some reports stating no sex difference (Bijur et al, 2008, Niesters et al, 2010 and others show morphine is less efficacious in females than males (Cepeda et al, 2003).…”
Section: Kurkinol and Kurkinorin Have Reduced Duration Of Action In Supraspinal Thermally Mediated Anti-nociceptionmentioning
confidence: 99%
“…Previous work suggests a role for sex hormones in opioid dependence and opioid reinforcing properties (Alexander et al, 1978;Bobzean et al, 2014;Cicero et al, 2003Cicero et al, , 2002bCicero et al, , 2002cHadaway et al, 1979;Harte-Hargrove et al, 2015;Serdarevic et al, 2017) , particularly in oral self-administration protocols (Stolerman and Kumar, 1972) . Sex differences are also apparent in the pharmacokinetic, metabolic, and analgesic effects of oxycodone (Chan et al, 2008;Holtman and Wala, 2006;Neelakantan et al, 2015) , and subtle differences have been observed in the liability for opioid abuse (Collins et al, 2016;Mavrikaki et al, 2017) . Therefore animal studies show that, relative to males, females self-administer more opioids, are more vulnerable to their reinforcing effects, and become more physically dependent, (Alexander et al, 1978;Boyer et al, 1998;Cicero et al, 2003Cicero et al, , 2002aGraziani and Nisticò, 2016b;Hadaway et al, 1979;Lofwall et al, 2012;Lynch, 2018;Lynch et al, 2002;Serdarevic et al, 2017) .…”
Section: Oxycodone 2-bottle Choice Highlights Sex Differences In Oxycmentioning
confidence: 99%